Dataset: Advancing towards cancer theragnostic by probing the ²²⁵Ac decay chain with ultra-high-resolution metallic magnetic calorimeter based detectors - Maurer, Kiara; Unger, Daniel; Béhé, Martin Peter; Knecht, Andreas; Schoeler, Katharina von; Hengstler, Daniel; Vitova, Tonya; Benešová-Schäfer, Martina; Fleischmann, Andreas; Gastaldo, Loredana; Wängler, Carmen; Enss, Christian; et al. (Universität, 2026)
This dataset contains the raw, unprocessed measurement data underlying the results presented in the publication: Advancing towards cancer theragnostic by probing the ²²⁵Ac decay chain with ultra-high-resolution metallic magnetic calorimeter based detectors Files The dataset is organized into two primary folders for the two measurement series: 2024_09-Tanzboden: Comparison measurements with ⁵⁵Fe 2024_09-Ac225: Measurements with ⁵⁵Fe and ²²⁵Ac, or ⁵⁵Fe, ²⁴¹Am, and ¹³³Ba For each measurement series, the combined metadata (summary.csv, settings.csv, and log.csv) as well as the data for the first measurement are provided. The full dataset, totaling approximately 0.8 TB, is long-time archived at heiARCHIVE and is available upon request. A measurement contains the individual triggered signals recorded from the MMC-based detector array. The processed spectra are not included here but are provided in the supplement dataset. For documentation on how to access, process, and analyze these raw measurements, please refer to the data analysis included in that supplement. Data Structure A measurement is a folder containing a Summary.txt file with general metadata, a Log.txt file with recording logs, and a subfolder for each ADC channel. Each ADC folder contains its configuration in ScopeSettings.txt as well as the folders POSP, BASE, and NEGP for positive, undefined, and negative polarity of the signals. Within the polarity folders, the signals are stored as *.sraw files inside *.zip archives. Each line of a *.sraw signal is defined by a specific identifier. Lines starting with H contain general header information formatted as H [Key]: [Value]. The line starting with S marks the binary stream containing the raw signal samples. Lines starting with C contain comments, formatted similarly to the header as C [Number]: [String]. Contact For questions regarding the dataset, or to request access to the full 0.8 TB raw data archive, please contact the corresponding authors of the publication.
Gesehen am 19.01.2026
Keywords: Forschungsdaten; Datenbank